SINTESIS DAN KARAKTERISASI NANOPARTIKEL PERAK TERMODIFIKASI KITOSAN MENGGUNAKAN REDUKTOR NaBH4 - Az Zahra, Upi Fathimah; Hindryawati, Noor; Panggabean, Aman Sentosa (Jurusan Kimia FMIPA UNMUL, 2024)
The research about synthesis of chitosan-modified silver nanoparticles using NaBH4 reducing agents has been carried out. This research aims to determine the optimum AgNO3 concentration, optimum pH and optimum stirring time. The chitosan-modified silver nanoparticles obtained were then characterized using a UV Vis Spectrophotometer, Particle Size Analyzer and Transmission Electron Microscopy instruments. The results of measurements using a UV-Vis Spectrophotometer, the synthesis of chitosan-modified silver nanoparticles was obtained was obtained at the optimum condition of AgNO3 concentration of 3x10-3 M, pH 4 and the optimum stirring time was 2 hours. The formation of AgNPs is characterized by the presence of typical absorption peaks at maximum wavelengths of 402 nm-434 nm. Keywords: Silver Nanoparticles, Chitosan, NaBH4